2015
DOI: 10.1021/acschembio.5b00218
|View full text |Cite
|
Sign up to set email alerts
|

Locked 2′-Deoxy-2′,4′-Difluororibo Modified Nucleic Acids: Thermal Stability, Structural Studies, and siRNA Activity

Abstract: 2′-Deoxy-2′,4′-difluorouridine (2′,4′-diF-rU) was readily incorporated into DNA and RNA oligonucleotides via standard solid phase synthesis protocols. NMR and thermal denaturation (T m) data of duplexes was consistent with the 2′,4′-diF-rU nucleotides adopting a rigid North (RNA-like) sugar conformation, as previously observed for the nucleoside monomer. The impact of this modification on T m is neutral when incorporated within RNA:RNA duplexes, mildly destabilizing when located in the RNA strand of a DNA:RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 52 publications
5
45
0
Order By: Relevance
“…Earlier reports of 4′- C -modified nucleotides, including 4′- C -OMe-2′-deoxynucleotides ( 17 , 18 ) and 2′-F,4′- C -F pyrimidine nucleotides ( 19–21 ) and their incorporation into oligonucleotides support the notion of a preference for a Northern sugar pucker. The thermodynamic stability of RNA duplexes containing such nucleotides is similar to that of the native counterparts ( 21 ). Indeed, we found that incorporation of 2′-F,4′- Cα -OMe-U ( Ufo , Figure 1 ) caused only minor changes to the melting temperature ( T m ) of RNA duplexes, whereby the modified ribose adopted a North ( N ) C3′- endo conformation in the crystal structure of a modified octamer ( 16 ).…”
Section: Introductionmentioning
confidence: 91%
“…Earlier reports of 4′- C -modified nucleotides, including 4′- C -OMe-2′-deoxynucleotides ( 17 , 18 ) and 2′-F,4′- C -F pyrimidine nucleotides ( 19–21 ) and their incorporation into oligonucleotides support the notion of a preference for a Northern sugar pucker. The thermodynamic stability of RNA duplexes containing such nucleotides is similar to that of the native counterparts ( 21 ). Indeed, we found that incorporation of 2′-F,4′- Cα -OMe-U ( Ufo , Figure 1 ) caused only minor changes to the melting temperature ( T m ) of RNA duplexes, whereby the modified ribose adopted a North ( N ) C3′- endo conformation in the crystal structure of a modified octamer ( 16 ).…”
Section: Introductionmentioning
confidence: 91%
“…It gave a mild destabilizing effect when incorporated in the RNA strand of DNA:RNA duplex and high destabilization when incorporated in the DNA strand of DNA:RNA and DNA:DNA duplex. Modification in the central region of guide strand with 2′,4′‐diF‐rU was more potent in silencing the gene expression …”
Section: Ribose Modificationsmentioning
confidence: 97%
“…Modification in the central region of guide strand with 2′,4′-diF-rU was more potent in silencing the gene expression. [27] siRNAs modified with 2′-O-methyl guanosine and uridine residues profoundly decreased the immunostimulation and interferon response. The effect of modification by 2′-O-methyl-4′-thioRNA (10) on gene silencing was studied against HeLa-Luc gene.…”
Section: Ribose Modificationsmentioning
confidence: 98%
See 2 more Smart Citations